Implementation of A Combination Training Progressive Muscle Relaxation Therapy and Music Therapy (Resik Therapy) to Decrease Hypertension in Datar Village, Sumbang District - Yulianto, Alfian Prasetya; Adinda, Nur; Karimah Nasr, Nailah; Fitriani, Alfina; Kodriyah, Kodriyah; Pramudita, Imelia Rizky; Lestari, Gita Ayu; Agustin, Herlina; Nabilah, Huria Husna; Kusumawardani, Lita Heni (CV Firmos, 2023)
Hypertension is a major factor causing human death globally. Various efforts have been made but not optimal. These conditions encourage academics to develop non-pharmacological therapies to complement pharmacological therapies, one of which is progressive muscle relaxation and music therapy. The combination of progressive muscle relaxation therapy and music therapy (RESIK) can inhibit vasoconstriction of blood vessels through baroreceptor stimulation. The purpose of this community service was to increase the prevention of high blood pressure in clients with hypertension in Datar Village, Sumbang District. There were 31 residents who took part in this activity, consisting of 31 women with an age range of 30-70 years. The main approaches used are lectures, discussions, demonstrations, and redemonstrations. The servant measures blood pressure in clients with hypertension first. Then the client was given RESIK therapy training for 30-45 minutes. After that the servant re-measures the client's blood pressure. The results of the service showed a decreased in blood pressure with an average initial systole score of 134 to 132, an average initial diastole score of 95 to 87. Therefore, partners received science and technology in an effort to lower blood pressure. Residents are expected to apply RESIK therapy to prevent hypertension to reduce the risk of complications such as stroke.